2015
DOI: 10.5219/478
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide selection signatures in Pinzgau cattle

Abstract: The aim of this study was to identify the evidence of recent selection based on estimation of the integrated Haplotype Score (iHS), population differentiation index (F ST ) and characterize affected regions near QTL associated with traits under strong selection in Pinzgau cattle. In total 21 Austrian and 19 Slovak purebreed bulls genotyped with Illumina bovineHD and bovineSNP50 BeadChip were used to identify genomic regions under selection. Only autosomal loci with call rate higher than 90%, minor allele frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Secondly, we used population differentiation (Fst) approach to identify the selection signatures in different breeds. Moreover, samples were also pruned for high LD SNPs using PLINK software version 1.9 (Purcell et al, 2007) and remaining 250,469 SNPs were used for selection signatures identification using population differentiation (Fst) method (Akey et al, 2002;Kasarda et al, 2015). To reduce the heterozygosity level in the data set of all the breeds, we used LD pruning as reported in some European and African zebu cattle breeds (Malkina et al, 2015).…”
Section: Identification Of Selection Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we used population differentiation (Fst) approach to identify the selection signatures in different breeds. Moreover, samples were also pruned for high LD SNPs using PLINK software version 1.9 (Purcell et al, 2007) and remaining 250,469 SNPs were used for selection signatures identification using population differentiation (Fst) method (Akey et al, 2002;Kasarda et al, 2015). To reduce the heterozygosity level in the data set of all the breeds, we used LD pruning as reported in some European and African zebu cattle breeds (Malkina et al, 2015).…”
Section: Identification Of Selection Signaturesmentioning
confidence: 99%
“…A selection signature is considered as an important genetic based approach in farm animals, especially in cattle (Tang et al, 2007). It provides a wide picture of evolutionary processes as well as complex functional information in the genome (Kasarda et al, 2015). This information helps in identification of effective loci for breeding programs and also for functional genomics annotation (Ismael et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they observed MSTN and FTO gene which are connected with beef production and thus were not preserved in our study with dairy and dual-purpose cattle. Kasarda et al (2015) found only 2 SNPs close to gene FTO using the integrated Haplotype Score (iHS) in Slovak and Austrian cattle. The highest peak (0.01%) between Slovak and Austrian on chromosome 23, between Slovak Pinzgau and Simmental on chromosome 4 and between Slovak Pinzgau and Holstein on chromosomes 1, 7 and 20 was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The same approach was utilized in this study to detect signatures of selection in common and different across populations. Kasarda et al (2015) identified the evidence of recent selection based on estimation of the iHS, F ST and characterized affected regions near QTL associated with traits under strong selection in Pinzgau cattle. Recent investigations of the structural variation in cattle genome suggest that selective forces, in addition to the genotypic and haplotypic patterns, operate on the copy number variation (CNV) in candidate genes and can be helpful to characterize the effects of domestication, breed formation and artificial selection (Perez O´Brian et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The iHS tests for Pinzgau cattle, which is a local breed of domestic cattle from the Pinzgau region of the federal state of Salzburg in Austria, showed that only seven regions had an iHS of >1.7 (Kasarda et al, 2015). This suggests that these commercial breeds have undergone stronger and more intensive selection pressure than Chinese Jinnan breed.…”
Section: Discussionmentioning
confidence: 99%